Analisis Efektivitas Biaya Penggunaan Kortikosteroid Inhalasi Pada Pasien Asma Rawat Jalan di Rumah Sakit - Shinta Nia Putri; Liza Pratiwi; Shoma Rizkifani (Journal Syifa Sciences and Clinical Research, 2022)
West Kalimantan is in the 6th highest order whose prevalence of asthma exceeds the national rate of 2.4% in 2018. Asthma therapy with inhaled corticosteroids that take a long time needs to be cost-effective so as not to increase the patient's immediate medical costs.  This study aims to determine the cost-effectiveness of using inhaled corticosteroids given to outpatients at Dr. Agoesdjam Hospital, Ketapang Regency. The study was conducted in a cross-sectional retrospective manner by taking data on patient medical records for the January-December 2020 period.  The sampling technique is carried out by purposive sampling. The pharmacoeconomic analysis carried out is Cost Effectiveness Analysis (CEA). The Average Cost Effectiveness Analysis (ACER) and Incremental Cost Effectiveness Analysis (ICER) methods  are used to analyze the most cost-effective inhaled corticosteroids. The results of the study were obtained with the characteristics of the study subjects based on gender the number of male patients n=23 (39%) and female n=36 (61%). The conclution of this research are the percentage of effectiveness of the use of inhaled corticosteroids at Dr. Agoesdjam Hospital, Ketapang Regency in 2020 is 33-100% and the most effective inhaled corticosteroids are flutiase combinations; Brotec; Combivent with an effectiveness of 100% with an ACER value of Rp. 731.45.